3D Interaction in Augmented Reality Environment with Reprojection Improvement on Active and Passive Stereo - Eko Budi Cahyono; Ilyas Nuryasin; Aminudin Aminudin (IC-ITECHS, 2014)
This research proposes the three dimensional (3D) interaction on the augmented reality (AR) environment based on interposition. Interposition is captured from the intersection of reconstruction points. That points should be increased to generate accurate interposition. The optimal triangulation is used to increase the performance for reconstructing 3D. This method is applied to Logitech camera (passive stereo) and Kinect camera (active stereo) to analyze the result of reconstruction. Based on the calibration testing, optimal triangulation gives a significant deference accuration on both of Logitech and Kinect cameras. On the passive stereo, accurate interaction is generated by combining subpixel detection and the optimal triangulation algorithm, while on the active stereo, the accuration of depth image can be improved by just applying the optimal triangulation algorithm.